Proceedings of the XXVII International Symposium on Lattice Field Theory — PoS(LAT2009) 2010
DOI: 10.22323/1.091.0120
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy $D^{*+}D^0_1$ scattering and the resonance-like structure $Z^+(4430)$

Abstract: Low-energy scattering of D * andD 1 meson are studied using quenched lattice QCD with improved lattice actions on anisotropic lattices. The calculation is performed within Lüscher's finitesize formalism which establishes the relation between the scattering phase in the infinite volume and the exact energy level in the finite volume. We obtain the scattering length a 0 = 2.52(47)fm and the effective range r 0 = 0.7(1)fm in J P = 0 − channel. Based on these results, it is argued that, albeit the interaction betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…[508,509]. The authors concluded that the interaction of D * andD 1 is attractive in the J P = 0 − channel but not strong enough to form a bound state [508,509].…”
Section: A Short Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…[508,509]. The authors concluded that the interaction of D * andD 1 is attractive in the J P = 0 − channel but not strong enough to form a bound state [508,509].…”
Section: A Short Summarymentioning
confidence: 99%
“…The authors concluded that the interaction of D * andD 1 is attractive in the J P = 0 − channel but not strong enough to form a bound state [508,509]. Both the phenomenological models [202,203,235,233] and the quenched lattice QCD calculations [508,509] indicated that the S-wave D 1D * interaction is attractive. The authors of Ref.…”
Section: A Short Summarymentioning
confidence: 99%